Estimating Gain in Efficiency in Complicated Randomized Response Surveys versus Simpler Alternatives (International Journal of Statistical Sciences, 2024)
Hartley and Ross’s (1954) ratio-type unbiased estimator for a finite population total based on a Simple Random Sample taken Without Replacement (SRSWOR) is examined for its performance versus the expansion estimator from the sample data at hand by Chaudhuri and Samaddar (2022). They also examined how Des Raj (1956) estimator based on PPSWOR performs against SRSWOR combined with expansion estimator using PPSWOR sample values. Here we study the expansion of them to Randomized Response survey data.International Journal of Statistical Sciences, Vol.24(1), March, 2024, pp 75-84